Influência da água no sistema de autolimpeza das esteiras condutoras de cortes sobre a qualidade microbiológica da carne de frango - Julião, Tatiana Aparecida [UNESP] (2014)
In poultry slaughterhouses, conveyor belts are common in meat handling areas. According to Brazilian legislation, cleaning of this equipment has to be done with heated and pressurized water. However, this process has been questioned based on the hypothesis that water might be responsible for propagation of microorganisms. This work aimed to compare microbial populations on the surface of conveyor belts (dry and wet) and on boneless chicken legs (consisting of thigh and drumsticks) in respect of heterotrophic aerobic mesophilic and psychrotrophic microorganisms, enterobacteria, Staphylococcus spp., Listeria spp. and Listeria monocytogenes. The samples were collected at two different moments and two points, at the beginning and end of the conveyor belts. Another objective of this study was to measure the amount of water used by the conveyor belts self-cleaning system during deboning. For such, 80 chiffonettes were collected from the conveyor belts surface (40 from dry equipment and 40 from wet equipment); and 80 samples, from boneless leg cuts (40 that were on the dry conveyor belt and 40 that were on the wet conveyor belt). Regarding mesophilic and psychrotrophic microorganisms, and enterobacteria, statistically significant differences were observed in terms of the populations found on the surface of the wet conveyor belt. The same was not observed for Staphylococcus spp. populations. It was also noticed greater isolation of Listeria spp. in samples from the dry conveyor belt. Comparing the two periods and sampling points, population of psychrotrophics was superior at the end of the conveyor belts and there were no statistically significant differences for the other microorganisms. Among cuts transported on dry or wet conveyor belts, in all moments and collecting points, statistically significant differences were not observed for the populations of the various microorganisms evaluated. Only for the psychrotrophic population ...